Approaches to Writing in EFL/ESL Context: Balancing Product and Process in Writing Class at Tertiary Level (Journal of NELTA, 2011)
This article presents the findings of an interventionist study designed to examine the effects of product and process approach to writing on learners' performance. Two ESL classes of United International University in Bangladesh participated in the study; initially one class was instructed to follow the method of writing of product approach, and the other received instruction on the process approach. Later a collaborative approach was adopted in both classes. Data were collected from the learners' performance in group works, discussions, observations of learners' strategy use, and from the end products. The findings indicate that the combination of product and process outperformed the presentation of the learners. There was corroborating evidence to support the view that the blend of both approaches tends to facilitate the learners to undertake a writing task to be developed. Finally, the advantages of using a product-process approach to gauging the effects of writing tasks are appraised.Key words: Teaching English writing; The process approach; The product approach; Incorporation of product process approach; Guided brainstorming; Top down approachJournal of NELTA Vol. 15 No. 1-2 December 2010Page: 77-88Uploaded date: 4 May, 2011DOI: 10.3126/nelta.v15i1-2.4612